The Application of Cell-Free Protein Synthesis in Genetic Code Expansion for Post-translational Modifications - Venkat, Sumana; Chen, Hao; Gan, Qinglei; Fan, Chenguang (Frontiers in Pharmacology, 2019)
The translation system is a sophisticated machinery that synthesizes proteins from 20 canonical amino acids. Recently, the repertoire of such composition has been expanded by the introduction of noncanonical amino acids (ncAAs) with the genetic code expansion strategy, which provides proteins with designed properties and structures for protein studies and engineering. Although the genetic code expansion strategy has been mostly implemented by using living cells as the host, a number of limits such as poor cellular uptake or solubility of specific ncAA substrates and the toxicity of target proteins have hindered the production of certain ncAA-modified proteins. To overcome those challenges, cell-free protein synthesis (CFPS) has been applied as it allows the precise control of reaction components. Several approaches have been recently developed to increase the purity and efficiency of ncAA incorporation in CFPS. Here, we summarized recent development of CFPS with an emphasis on its applications in generating site-specific protein post-translational modifications by the genetic code expansion strategy.